Epistemiczny układ odniesienia teorii inteligentnego projektu - Jodkowski, Kazimierz (Filozofia Nauki, 2006)
Intelligent design theory is accused of being a hidden form of creationism. Evolutionism and creationism are formulated in different epistemic frameworks. The author wants to answer the question whether the accusation mentioned above is right. The theory does not indicate the source of design. It only postulates the possibility of detecting the design in nature. The identification of the designer is not possible with the help of scientific methods. Therefore, intelligent design theory is compatible both with naturalistic and creationist epistemic frameworks.